2012
DOI: 10.1071/sh11118
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and behaviours of health care workers towards clients of sexual health services in Fiji

Abstract: A cross-sectional survey was conducted to identify the attitudes and behaviours of health care workers (HCWs) in health care settings (HCS) in Fiji involving 369 participants. Self-rated knowledge of HIV and sexually transmissible infections (STIs) varied depending on whether the HCS was divisional or sub-divisional, and varied between the various national divisions. HCWs with experience in HIV, reproductive health and antenatal clinics had higher self-rated HIV knowledge. A high proportion had a fear of catch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In the current study there were 93.4% who have never attended any occupational training program regarding AIDS or HIV prevention. The findings compare favourably with those reported from other research (Adelekan et al, 1995;Ugochukwu ,2003;Lui et al .,2012 ) . They had also found that important knowledge gaps and appreciation of occupational training programs in all health categories which they considered.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study there were 93.4% who have never attended any occupational training program regarding AIDS or HIV prevention. The findings compare favourably with those reported from other research (Adelekan et al, 1995;Ugochukwu ,2003;Lui et al .,2012 ) . They had also found that important knowledge gaps and appreciation of occupational training programs in all health categories which they considered.…”
Section: Resultssupporting
confidence: 88%
“…So many studies have been done which were aimed to assess the attitude towards HIV/AIDS. Most of the literature indicated negative findings (Lui et al, 2012;Dieleman et al, 2007) and few others gave the positive findings.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of occupationally acquired HIV infection is rare compared with transmission of infections such hepatitis B and this needs to be highlighted to students [28]. Negative attitudes held by future professionals can contribute to continued stigma and discrimination towards PLHIV and key at-risk populations, a recognized barrier to universal access and prevention of new infections in Fiji and the Pacific [33]. Interestingly, the majority of students believe the misconception that all health professionals have the right to know a patient's HIV status for their own safety.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous organisation of selected actors within the community, with the aim of developing prevention and responding more effectively to those in need during crises, is a recurrent feature in many islands. During the peak of the spread of HIV/AIDS, senior health management in public health organisations in Fiji implemented 'independent' prevention and information programs to tackle HIV/AIDS, actively coordinating with other actors within the community [54]. These actions promoted the overall need to have a more holistic and general framework on promoting and coordinating responses from community members, which would not be limited to HIV/AIDS but would also be applied to other future crises [54].…”
Section: Community Actionmentioning
confidence: 99%
“…During the peak of the spread of HIV/AIDS, senior health management in public health organisations in Fiji implemented 'independent' prevention and information programs to tackle HIV/AIDS, actively coordinating with other actors within the community [54]. These actions promoted the overall need to have a more holistic and general framework on promoting and coordinating responses from community members, which would not be limited to HIV/AIDS but would also be applied to other future crises [54]. Furthermore, during the COVID-19 crisis, spontaneous initiatives led by indigenous Maori effectively addressed the challenges in Aotearoa, New Zealand [55].…”
Section: Community Actionmentioning
confidence: 99%